The Effect of Remuneration and Work Motivation on the Performance of Administrative Employees - Stevani Fransy Gillis Kaparang; Stephen Sampe; Very Y. Londa (Newinera Publisher, 2024)
This study aims to determine and analyze the effect of Remuneration and Work Motivation on the Performance of Administrative Employees at RSUP Prof. Dr. R. D. Kandou. This study used a quantitative approach. The population in this study was administrative employees at RSUP Prof. Dr. R. D. Kandou. The sampling technique uses a simple random sampling technique. Data collection techniques by distributing questionnaires, while secondary data through literature studies by reading various literature. Data analysis techniques use Research Instrument Test (validity and reliability test), t test, F test, r square test and multiple linear regression analysis with the help of SPSS software. The results of this study show that: (1) Remuneration has a positive and significant effect on performance; (2) Work Motivation has a positive and significant effect on Performance; (3) Remuneration and Work Motivation have a positive and significant effect on Performance. The performance of administrative employees at RSUP Prof. Dr. R. D. Kandou is influenced by remuneration of 41.4% and work motivation of 31.4%. It is partially concluded that the variable of Work Motivation most dominantly affects the Performance of Administrative Employees. Suggestions that can be conveyed to RSUP Prof. Dr. R. D. Kandou that it is necessary to continue to monitor and evaluate employee performance so that the services provided to the community are maximized. Moreover, motivation at work is one of the factors that can improve the performance of administrative employees at RSUP Prof. Dr. R. D. Kandou.